INFLUENCE OF CONTACT STATE ON PROPAGATION PATH OF RAIL SURFACE CRACK - MENG RuiJun; ZHAO Rui; WEI XiaoGang (Jixie qiangdu)
In order to investigate the formation mechanism of fishhook shaped spalling defect on rail surface, the fatigue calculation model of wheel/rail rolling contact was established and the prediction method of crack propagation path was proposed based on the contact element method and maximum circumferential tensile stress criterion. And the influence of wheel/rail contact state and multiple cracks on crack propagation path were analyzed. The results show that, the initial rail surface microcrack is an I-Ⅱ mixed crack, and gradually tends to propagate in the 90° direction. When the crack grows to a certain depth, the driving force of crack propagation changes from KI to KⅡ. At this point, the crack tip will turn about 70° under the drive of KⅡ, and tends to propagate upward and leads to fishhook shaped spalling defect. The characteristics of wheel/rail tangential loads have a great influence on the spalling path, and the maximum depth of spalling defect can be up to 1.76 mm under the traction condition. When there are multiple cracks on the rail surface, the sliding driving effect of the middle crack will be strengthened. Finally, the intersection between adjacent cracks will form, and accelerates the formation of spalling defect.